The Socioeconomic Implications of Government Initiatives on the Organic Vegetable Production in Los Baños, Laguna - Kyle Cristel D. Morada; Chester Alexis C. Buama; Desiree L. Wagan; Regina E. Gloria; Marie Ann Gonzales; Bayani A. Guia (Humanities, Society, and Community, 2026)
The global demand for organic produce has risen due to health and wellness trends, driving the expansion of organic vegetable production. In the Philippines, government efforts have aimed to increase organic farming by providing various forms of public support. This study aims to assess the social and economic implications of the government initiatives on organic vegetable production in Los Baños, Laguna. It profiles farmers by age, sex, education, civil status, income source, organization affiliation, experience, and farm size. The study also examines government support in education, capacity building, farm inputs, financial incentives, infrastructure, regulation, and marketing. Data from 34 farmers were collected through structured questionnaires and analyzed using descriptive statistics and thematic analysis. Most farmer-respondents are married and aged 40-60 years; there are more females than males. All the farmers have had formal schooling, most of whom are secondary graduates. Their primary source of income is farming, including the cultivation of organic vegetables; hence, they are members of the existing association in the municipality. They have existing knowledge of organic vegetable production even before the government's plans and interventions on organic vegetables were implemented. Their farms measure one hectare or less for organic vegetable production. Government interventions have positively influenced their organic vegetable production both socially and economically. However, further targeted support is needed, including age-specific programs, gender-responsive initiatives, better education and training, infrastructure development, and improved market access. Recommendations to implement government initiatives effectively include implementing one-package-deal programs, continuous monitoring, transparency, shared learning, and investment in research and development.